نحو إستراتيجية جديدة في تدريس مهارة الاستماع وأساليب تدريسها في التعليم اللغة العربية - Prihartini, Yogia; Buska, Wahyudi (Al-Uslub: Journal of Arabic Linguistic and Literature, 2019)
الاستماع هو استقبال الصوت مع متابعة باهتمام وهو أحد عمليتي الاتصال بين بني البشر، كما أنه وسيلة التثقيف وتلقي المعلومات. فهو فن يشتمل على عملية معقدة في طبيعتها. فإنه ليس مجرد سماع، فهو عبارة عن عملية يعطي فيها المستمع اهتماما خاصا وانباها مقصودا لما يتلقاه أذنه من الأصوات. ومن ثم كان الاستماع له مكانته الرئيسية بل هو أهم المهارات اللغوية الأربعة على الإطلاق وهي: الاستماع، والكلام، والكتابة، والقراءة. وذلك لأن المتكلم لاينطق إلا من خلال الاستماع الجيد، وهكذا العكس. فالمستمع الجيد هو بالضرورة متحدث جيد، والمتحدث الجيد هو بالضرورة مستمع جيد The researh is aimed to analyze the strategy of listening skill learning in Arabic. Listening is the reception of sound with follow-up with interest and it is one of the two processes of communication between humans, and it is also a means of education and receiving information. It is an art that involves a complex process in its nature. It is not just a hearing, it is a process in which the listener gives special attention and intentional attention to the sounds his ear receives. Hence listening was his main position, but rather the most important of the four language skills ever: listening, speaking, writing and reading. This is because the speaker only speaks through good listening, and so on. A good listener is necessarily a good speaker, and a good speaker is necessarily a good listener.